2022
DOI: 10.1021/acs.orglett.2c02974
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide-Based Ligand-Directed Chemistry Enables Protein Functionalization

Abstract: The ligand-directed (LD) chemistry provides powerful tools for site-specific modification of proteins. We utilized a peptide with an appended methionine (Met) as a ligand; then, the Met thioether was modified into sulfonium which enabled a proximity induced group transfer onto protein cysteine in the vicinity upon peptide−target binding. The sulfonium warhead could be easily constructed with unprotected peptides, and the transferable group scope was conducted on model protein PDZ and its ligand peptides. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Achieving a versatile reaction platform requires a good structural diversity and a thorough understanding of the structure–activity relationship (SAR), which by regulating the stability and cleavability of the bioconjugates and stapled peptides could enable fine-tuning of biological activity. Our group has recently investigated the unique reducibility and biophysical properties of positively charged compounds, such as sulfoniums and pyridiniums, making them promising candidates for bioconjugation. Aromatic nucleophilic substitute (S N Ar) reactions have been extensively researched and applied within the realm of bioconjugation chemistry, with reports showcasing the substantial potential of such reagents when employing nitrogen-containing heterocycles and their onium salts as conjugation reagents. Drawing on the in-depth understanding of these electron-deficient compounds, we identified that pyridiniums with halogen as a leaving group would be a suitable platform for tunable bioconjugation through the S N Ar. The electrophilicity of the halo-pyridiniums could be predicted and finely tuned by altering the effective nuclear charge, owing to the well-understood electron effects of substituents on aromatic rings .…”
Section: Introductionmentioning
confidence: 99%
“…Achieving a versatile reaction platform requires a good structural diversity and a thorough understanding of the structure–activity relationship (SAR), which by regulating the stability and cleavability of the bioconjugates and stapled peptides could enable fine-tuning of biological activity. Our group has recently investigated the unique reducibility and biophysical properties of positively charged compounds, such as sulfoniums and pyridiniums, making them promising candidates for bioconjugation. Aromatic nucleophilic substitute (S N Ar) reactions have been extensively researched and applied within the realm of bioconjugation chemistry, with reports showcasing the substantial potential of such reagents when employing nitrogen-containing heterocycles and their onium salts as conjugation reagents. Drawing on the in-depth understanding of these electron-deficient compounds, we identified that pyridiniums with halogen as a leaving group would be a suitable platform for tunable bioconjugation through the S N Ar. The electrophilicity of the halo-pyridiniums could be predicted and finely tuned by altering the effective nuclear charge, owing to the well-understood electron effects of substituents on aromatic rings .…”
Section: Introductionmentioning
confidence: 99%
“…Significant efforts have been devoted to modification of residues and characterization of reactive residues in the proteome (e.g., cysteine, 1-3 lysine, 4,5 methionine, 6 and histidine 7 residues), to increase our understanding of contemporary biological and pharmaceutical sciences. [8][9][10][11][12][13][14][15] Cysteine is the most nucleophilic residue in the human proteome and shows high reactivity in various biochemical functions. Cysteine proteases, also known as thiol proteases, constitute one of the diverse families of functional enzymes.…”
mentioning
confidence: 99%